THE EFFECT OF FLUID VARIATIONS IN THE RESERVOIR ON AIR PRESSURE IN KNIFE TOOL HEATING FURNACES - Ramadhan, Muhammad Rizki; Firizal, Harlin; Hermawan, Rudi; Ramadhan, Anugrah Agung; Setiyo, Edi; Susiloningsih, Esti (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
The stainless steel material reservoir tube can produce combustion steam from the heating furnace. The research objective was to determine the effect of variations in the type of liquid and air pressure efficiently used in the reservoir tube. The type of research used is pure experimental research. The medium used is mineral water, 10%, 20%, and 30% brine, and the Manufacturer's coolant is heated using a heating furnace at 110° C for 42 minutes and measured by a pressure gauge. The results of the tests carried out have the effect of differences in mineral water 1.50 bar or 1.48 atmosphere, 10% brine 1.50 bar or 1.48 atmosphere, 20% brine 2.40 bar or 2.36 atmosphere, 30% brine 3, 50bar or 3.45 atmospheres, factory coolant 1.75bar or 1.72 atmospheres. 30% salt water is more efficient and suitable for the stainless steel material reservoir heating process in producing steam under pressure, which is used in knife tools.